2016
DOI: 10.15287/afr.2016.497
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of soil respiration, carbon balance and root carbon use efficiency in two managed Moso bamboo forests in subtropical China

Abstract: Tang X., Fan S., Qi L., Guan F., Su W., Du M., 2016. A comparison of soil respiration, carbon balance and root carbon use efficiency in two managed Moso bamboo forests in subtropical China. Ann. For. Res. 59(1): 3-20.Abstract. Moso bamboo forest (Phyllostachys heterocycla [Carr.] Mitford cv. Pubescens) is an important forest type in subtropical China and comprises an important pool in the global carbon cycle. Understanding the effects of the stand management, such as understory removal, on soil respiration (RS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 60 publications
(103 reference statements)
2
11
0
Order By: Relevance
“…Additionally, plots of soil respiration against daily temperature patterns show a rather flat relationship for the summer with a strong hysteresis. Similar findings have been reported in Moso bamboo forest of subtropical China by Tang et al (2016) and Song et al (2013) . Depth of the soil temperature measurement affected the explanatory power of soil temperature.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, plots of soil respiration against daily temperature patterns show a rather flat relationship for the summer with a strong hysteresis. Similar findings have been reported in Moso bamboo forest of subtropical China by Tang et al (2016) and Song et al (2013) . Depth of the soil temperature measurement affected the explanatory power of soil temperature.…”
Section: Discussionsupporting
confidence: 90%
“…In the eastern Amazon forest, similar results were obtained [42][43]. Specifically, enhanced precipitation reduces fine root production and brings a decreasing GPP in the alpine grassland ecosystem, increased respiration of leaf and root, and decreased NPP [38][39]. However, the correlation was not obvious in dry, cold areas and warm and humid areas [10,24,44].…”
Section: Responses Of Cue To Variation Of Environmental Factors In DIsupporting
confidence: 60%
“…4) shows that climate factors play a remarkable role in the alpine grassland (alpine steppe and alpine meadow) of the border region between Tibet and Qinghai (Figs 4d-f). The findings indicated that precipitation, temperature, and aridity index promotes CUE of alpine grasslands [3], and the responses of CUE to these factors were different in the different grassland ecosystem [1,3,13,38].…”
Section: Responses Of Cue To Variation Of Environmental Factors In DImentioning
confidence: 99%
See 1 more Smart Citation
“…In each plot, the diameter at breast height (DBH, 1.3 m), height and age of all bamboos were measured and recorded. The age was expressed by "du", which reflected the phenomenon of "on-year" and "off-year" in moso bamboo forests [17,18]. In an "on-year", more than 90% of new shoots were produced, followed by a few new shoots in an "off-year", because moso bamboo forests produced new shoots at two-year intervals [19].…”
Section: Soil Samplingmentioning
confidence: 99%